Numerical simulation on the centre macrosegregation during Billet continuous casting with the soft reduction. (21st October 2022) - Ma, Haitao; Zhang, Jiongming; Yin, Yanbin; Yan, Zhaozhao; Liu, Huayang
ABSTRACT: To investigate the effect of soft reduction on the centre macrosegregation during the continuous casting process, a mathematical model coupling flow, solidification and species transfer was developed. Moreover, a soft reduction model had been incorporated into the coupling model. The solidification model was validated by methods of the billet surface temperature measurement and the tracer experiment. The predicted results revealed that the carbon enrichment occurred at the solidification front during the solidification process of the molten steel. The centre segregation ratio was 1.2 in the billet centre without soft reduction. The calculation results and experimental results showed that the centre segregation ratio at the centre solidification fraction of 0.3 with soft reduction was 1.11 and 1.09, respectively. The experimental results with the soft reduction at the centre solidification fraction of 0.3 had a good agreement with the calculation results.